Association of Diet and Calcium Tartrate Tetrahydrate Uroliths in Dogs - Jody Lulich; Lori Koehler; Lisa Ulrich; Eva Furrow (Journal of Veterinary Internal Medicine)
ABSTRACT Background Calcium tartrate tetrahydrate (CTT) uroliths are recently identified in dogs. Objectives To report on the types and prevalence of diets, supplements, and medications containing salts of tartaric acid consumed by dogs with CTT urolithiasis. Animals Sixty‐three client‐owned dogs identified with CTT uroliths from a single urolith analysis laboratory. Methods Retrospective case series evaluating dogs with CTT uroliths and their prevalence of consuming diets, supplements, and medications containing salts of tartaric acid before diagnosis of urolithiasis. Results Dogs with CTT uroliths were predominantly male (53/63, 84%) small purebreds (48/63, 76%). Thirty‐three of 63 cases provided additional information by completing our survey. In 25 of 33 (76%) cases, a source of tartaric acid was identified in diets, supplements, or medications. In 24 of these 25 cases (96%), the source of tartaric acid was choline bitartrate. Conclusions When investigating a cause for CTT uroliths in dogs, consider diets and supplements containing choline bitartrate as a potential source of urolith components.